Thoracic rat spinal cord contusion injury induces remote spinal gliogenesis but not neurogenesis or gliogenesis in the brain - Franz, Steffen; Ciatipis, Mareva; Pfeifer, Kathrin; Kierdorf, Birthe; Sandner, Beatrice; Bogdahn, Ulrich; Blesch, Armin; Winner, Beate; Weidner, Norbert (PLoS ONE, 2014)
After spinal cord injury, transected axons fail to regenerate, yet significant, spontaneous functional improvement can be observed over time. Distinct central nervous system regions retain the capacity to generate new neurons and glia from an endogenous pool of progenitor cells and to compensate neural cell loss following certain lesions. The aim of the present study was to investigate whether endogenous cell replacement (neurogenesis or gliogenesis) in the brain (subventricular zone, SVZ; corpus callosum, CC; hippocampus, HC; and motor cortex, MC) or cervical spinal cord might represent a structural correlate for spontaneous locomotor recovery after a thoracic spinal cord injury. Adult Fischer 344 rats received severe contusion injuries (200 kDyn) of the mid-thoracic spinal cord using an Infinite Horizon Impactor. Uninjured rats served as controls. From 4 to 14 days post-injury, both groups received injections of bromodeoxyuridine (BrdU) to label dividing cells. Over the course of six weeks post-injury, spontaneous recovery of locomotor function occurred. Survival of newly generated cells was unaltered in the SVZ, HC, CC, and the MC. Neurogenesis, as determined by identification and quantification of doublecortin immunoreactive neuroblasts or BrdU/neuronal nuclear antigen double positive newly generated neurons, was not present in non-neurogenic regions (MC, CC, and cervical spinal cord) and unaltered in neurogenic regions (dentate gyrus and SVZ) of the brain. The lack of neuronal replacement in the brain and spinal cord after spinal cord injury precludes any relevance for spontaneous recovery of locomotor function. Gliogenesis was increased in the cervical spinal cord remote from the injury site, however, is unlikely to contribute to functional improvement.
EVALuna2:26226